Contribution to the quantitative study of violence in Algerian hospital environment - Heddar, Yamina; Djebabra, Mébarek; Saadi, Saadia (11th Annual International Conference on Industrial Engineering and Operations Management, 2021)
The workplace, and more particularly the healthcare sector, has recently experienced a staggering increase in violence. These aggressive behaviors are resulting in considerable consequences on healthcare workers, both in terms of mental and physical health. In light of this observation, this study aims to provide a quantitative analysis of the potential causes leading to violence in Algerian hospitals, which have become the place where tensions arise, especially during these uncertain times caused by the COVID-19 pandemic. Therefore, we started with conducting a field survey, in order to highlight the main causes behind this violence, as well as the strategy in terms of how it is managed as a risk. Then we used ISHIKAWA diagrams to classify predefined causes into several categories and anticipate the likelihood of such violent behaviors. Finally, the results of this study revealed that working conditions were the main cause of violence in Algerian hospitals. In order to remedy this gap, we recommend improving the healthcare staff well-being, as well as prioritizing proactive measures preventing violent behaviors.